Nonlinear control of direct-drive pump-controlled clutch actuator in consideration of pump efficiency map. (October 2019) - Gao, Bingzhao; Li, Xin; Zeng, Xiaohua; Chen, Hong
Abstract: Pump-controlled hydraulic system, compared with the valve-controlled one, has simplified structure and increased efficiency, but the dynamic response is poor. This paper presents a high precision, fast dynamic response, and computational low-cost controller for a novel direct-drive pump-controlled hydraulic system. Firstly, the pump efficiency map is proposed to consider the nonlinear characteristic of the pump due to the time-varying friction and leakage, which makes the control design a challenging task. Then, a triple-step control strategy is proposed to deal with this design difficulty, considering the friction and leakage. Finally, the designed controller is evaluated through simulation and experimental tests. The results show that the settling time is 0.25 s without overshoot and the steady error is within ± 0.1 mm, which are hardly achieved by the traditional control method. The outstanding performance of the proposed system will extend the applications of the pump-controlled hydraulic system, such as to the clutch actuation system of Automated Manual Transmission.